Analisis Penggunaan Aplikasi Shopee Terhadap Minat Belanja Mahasiswa Ekonomi Syariah IAIN Pontianak - Inahuhidayah, Siti Nor; Nurmasita, Utin Deasy; Gunawan, Muhammad Wawan; Handayani, Tri Sedya; Yati, Yati; Adiningrum, Selvia (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to identify and analyze factors that influence the use of the Shopee application among university students. This research uses qualitative research methods through a descriptive approach. This research data was collected using data collection techniques in the form of observation and in-depth interviews and then analyzed. A number of students from the class of 2021 of the Sharia Economics study program who were research subjects in this study were interviewed regarding online shopping behavior using the Shopee application. The results show that Shopee is an online shopping application that meets students' needs with attractive offers, provides the benefits of shopping anytime and anywhere at more affordable prices through promotions, apart from that Shopee also has a negative impact on students' consumptive behavior. The use of Shopee by students is considered to provide convenience and attractive offers. This research is hoped to be useful and contribute in increasing the understanding of this topic and can be used as a reference for economic actors, students and other related parties